The Influence of Work Family Conflict, Work Life Balance, and Authentic Leadership on Employee Performance at Swiss-Bel Hotel Rainforest Kuta - Dewi, Ida Ayu Kusuma; Mulyadi, Made (Jurnal Ilmiah Sumber Daya Manusia, 2025)
Human resources are a key element in the success of an organization. The success of a company heavily relies on the quality of its human resources. Achieving organizational goals is not only determined by technology but, more importantly, by the individuals who carry out the work. This study aims to analyze the effect of work family conflict, work life balance, and authentic leadership on employee performance at Swiss-Bel Hotel Rainforest Kuta. A quantitative approach was used in this research. The population of this study consists of all employees of Swiss-Bel Hotel Rainforest Kuta, totaling 72 employees, with a saturated sampling technique. Data were collected through documentation and questionnaires, and the data analysis technique employed was multiple linear regression. The results of the study indicate that work family conflict, work life balance, and authentic leadership have a positive impact on employee performance. Simultaneously, these three variables also significantly affect employee performance.